Identification of recent temperature breaks and trends: example in West Africa and in the Gulf of Guinea - (:unkn) unknown (My University, 2015)
In the present context of environmental and climatic change, any trend in meteorological parameters, especially in temperature,is often discussed. This work aims to evaluate long term temperature trends and break points at two weather stations in WestAfrica (Niamey / Niger and Abidjan / Ivory Coast) and for sea surface temperatures (SSTs) in the Gulf of Guinea. The objective is to examine whether the model predictions of the fifth IPCC assessment report (2013) are consistent with observations and if the evolution of meridian thermal gradients will impact the West African monsoon in a context of global atmospheric and oceanic warming. Various heterogeneities are detected in the series: thermal break points are clearly identified in Niamey and Abidjan, in 1983 and 1986, respectively. After the mid-1980s, annual temperature anomalies show significant warming trends while equatorial Atlantic SST does not present any significant break point. It is however found that the large scale contrast of temperatures between the ocean and the continent represented by the series have increased by 0.07°C per decade during the last 30 years.
Keywords: African Research